2021
DOI: 10.1017/sjp.2021.12
|View full text |Cite
|
Sign up to set email alerts
|

How Digital Technologies Modify The Work Characteristics: A Preliminary Study

Abstract: New technologies with unprecedented agentic capabilities (i.e., action selection, protocol development) are now introduced in organizations such as Big Data, 3D printing or artificial intelligence. Because they are endowed with novel capabilities that might compete with human agency, they might disrupt the way employees work. Based on the work design model, this study aims to examine their introduction in the daily work activities and the consequent perceptions of the work characteristics. Building on Murray’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 93 publications
0
10
0
Order By: Relevance
“…In the context of knowledge characteristics, new qualifications and specialized knowledge are required for the effective use of ICT (Fréour et al. 2021 ; Pfeiffer 2018 ). Otherwise, remote work could result in a simplification of work activities, which might lead to less task variety, with a subsequent reduction in intrinsic motivation (Kunst 2019 ; Szalavetz 2021 ).…”
Section: Definition Of Mobile Workmentioning
confidence: 99%
“…In the context of knowledge characteristics, new qualifications and specialized knowledge are required for the effective use of ICT (Fréour et al. 2021 ; Pfeiffer 2018 ). Otherwise, remote work could result in a simplification of work activities, which might lead to less task variety, with a subsequent reduction in intrinsic motivation (Kunst 2019 ; Szalavetz 2021 ).…”
Section: Definition Of Mobile Workmentioning
confidence: 99%
“…Job control or autonomy is therefore known as a fundamental task characteristic and has the potential to enhance job performance and increase motivation (Gagné et al, 1997 ; Morgeson et al, 2005 ; Ter Hoeven et al, 2016 ). However, technological developments and innovations, such as artificial intelligence, give rise to new possibilities for task automation that have the capability to fundamentally change the workers' perceived level of autonomy (Arntz et al, 2020 ; Wang et al, 2020 ; Fréour et al, 2021 ). Overall, it has been shown that automation can either benefit or decrement workers' performance and wellbeing, depending on the task itself, the organizational structure/environment, design implementation and the machine's level of autonomy (Wiener and Curry, 1980 ; Kaber and Endsley, 1997 , 2004 ; Parasuraman et al, 2000 ; Arntz et al, 2020 ).…”
Section: Theories and Models On Human In Controlmentioning
confidence: 99%
“…The development of recent technologies, such as artificial intelligence (AI) or advanced robotics has established new possibilities for task automation and revived the debate on work-related psychosocial and organizational aspects and on workers' safety and health. Amongst other things, these new technologies have the capability to fundamentally change the workers' perceived level of autonomy (Arntz et al, 2020 ; Wang et al, 2020 ; Fréour et al, 2021 ). The reason lies within a key feature of modern AI, its ability to operate and adapt without human intervention, in other words, autonomously while the human is left with supervisory or ancillary activities.…”
Section: Introductionmentioning
confidence: 99%
“…Fenner and Renn 2010;Johnson et al 2020) and therefore might reduce the perceived autonomy. The use of these technologies also enables greater monitoring and control of employees and the work process, which reduces autonomy (Cascio and Montealegre 2016;Fréour et al 2021;Gerten et al 2018).…”
Section: Work Design and Smart Technologiesmentioning
confidence: 99%
“…This can be explained as increasing digitalization and automation leads to more complex processes. In order to be able to fix faults in such complex systems, employees need specialized knowledge (Fréour et al 2021;Pfeiffer 2018a). In addition, smart technologies can provide relevant information to employees, enabling learning on the job, accomplishing more complex and diverse tasks, or greater participation in problem-solving processes (Blumberg and Kauffeld 2020;Szalavetz 2021).…”
Section: Work Design and Smart Technologiesmentioning
confidence: 99%